Exome Sequencing Data Analysis and a Case-Control Study in Mexican Population Reveals Lipid Trait Associations of New and Known Genetic Variants in Dyslipidemia-Associated Loci - Jurado-Camacho, Pedro A.; Cid-Soto, Miguel A.; Barajas-Olmos, Francisco; García-Ortíz, Humberto; Baca-Peynado, Paulina; Martínez-Hernández, Angélica; Centeno-Cruz, Federico; Contreras-Cubas, Cecilia; González-Villalpando, María Elena; Saldaña-Álvarez, Yolanda; Salas-Martinez, Guadalupe; Mendoza-Caamal, Elvia C.; et al. (Frontiers in Genetics, 2022)
Background. Plasma lipid levels are a major risk factor for cardiovascular diseases. Although international efforts have identified a group of loci associated with the risk of dyslipidemia, Latin American populations have been underrepresented in these studies. Objective. To know the genetic variation occurring in lipid-related loci in the Mexican population and its association with dyslipidemia. Methods. We searched for single-nucleotide variants in 177 lipid candidate genes using previously published exome sequencing data from 968 unrelated Mexican individuals. With the extracted variants, we performed a case-control study. Logistic regression and quantitative trait analyses were implemented in PLINK software. Haplotype analyses were performed with the Haploview software. Results. Among the 8405 biallelic variants identified in our sample population, 14.67% showed a frequency >0.01. We found 75 variants in 38 genes significantly associated with at least one lipid trait, with the most significant associations found in the APOA1/C3/A4/A5-ZPR1-BUD13 gene cluster on chromosome 11. Notably, 15 out of 23 variants associated with HTG were within this cluster. We also found several novel variants associated with different lipemic traits: HTG: rs3825041 in BUD13; HTC: rs139047 in PNPLA3 and rs4888167 in CMIP; low HDL-C: rs2254537 in GPAM; and high LDL-C: rs2723501 in SNX13, rs5909 in HMGCR, and rs2292642 in PGS1. In addition, we found a haplotype composed of the variants rs1169288, rs2464196, and rs2464195 in HNF1A, associated with low HDL-C. Conclusions. We identified novel variants in lipid-regulation candidate genes in the Mexican population, an underrepresented population in genomic studies, demonstrating the necessity of more genomic studies on multi-ethnic populations to gain a deeper understanding of the genetic structure of the lipemic traits.